Evaluation of targetable biomarkers for chimeric antigen receptor T-cell (CAR-T) in the treatment of pancreatic cancer: a systematic review and meta-analysis of preclinical studies: Pancreatic cancer is one of the lethal malignant tumours in the world. In this study, we investigated the CAR T-Cell therapy of pancreatic cancer. (2nd September 2020) - Sahlolbei, Maryam; Dehghani, Mohsen; Kheiri yeghane azar, Behghat; Vafaei, Somayeh; Roviello, G; D'Angelo, Alberto; Madjd, Zahra; Kiani, Jafar
Abstract: One of the cutting edge techniques for treating cancer is the use of the patient's immune system to prevail cancerous disease. The versatility of the chimeric antigen receptor (CAR) T-cell approach in conjugation with promising treatments in haematological cancer has led to countless cases of research literature for the treatment of solid cancer. A systematic search of online databases as well as gray literature and reference lists of retrieved studies were carried out up to March 2019 to identify experimental animal studies that investigated the antigens targeted by CAR T-cell for pancreatic cancer treatment. Studies were evaluated for methodological quality using the SYstematic Review Center for Laboratory Animal Experimentation bias risk tool (SYRCLE's ROB tool). Pooled cytotoxicity ratio/percentage and 95% confidence intervals were calculated using the inverse-variance method while random-effects meta-analysis was used, taking into account conceptual heterogeneity. Heterogeneity was assessed with the Cochran Q statistic and quantified with the I 2 statistic using Stata 13.0. Of the 485 identified studies, 56 were reviewed in-depth with 16 preclinical animal studies eligible for inclusion in the systematic review and 11 studies included in our meta-analysis. CAR immunotherapy significantly increased the cytotoxicity assay (percentage: 65%; 95% CI: 46%, 82%). There were no evidence for significant heterogeneity across studies [ P = 0.38 ( Q statistics), I 2 = 7.14%] and for publication bias. The quality assessment of included studies revealed that the evidence was moderate to low quality and none of studies was judged as having a low risk of bias across all domains. CAR T-cell therapy is effective for pancreatic cancer treatment in preclinical animal studies. Further high-quality studies are needed to confirm our finding and a standard approach of this type of studies is necessary according to our assessment.